Utility of the Youth Compendium of Physical Activities. Issue 3 (3rd July 2018) - Ainsworth, Barbara E.; Watson, Kathleen B.; Ridley, Kate; Pfeiffer, Karin A.; Herrmann, Stephen D.; Crouter, Scott E.; McMurray, Robert G.; Butte, Nancy F.; Bassett, David R.; Trost, Stewart G.; Berrigan, David; Fulton, Janet E.
ABSTRACT: Purpose : The purposes of this article are to: (a) describe the rationale and development of the Youth Compendium of Physical Activities (Youth Compendium); and (b) discuss the utility of the Youth Compendium for audiences in research, education, community, health care, public health, and the private sector.Methods : The Youth Compendium provides a list of 196 physical activities (PA) categorized by activity types, specific activities, and metabolic costs (youth metabolic equivalents of task [METy ]) as measured by indirect calorimetry. The utility of the Youth Compendium was assessed by describing ways in which it can be used by a variety of audiences.Results : Researchers can use METy values to estimate PA levels and determine changes in PA in intervention studies. Educators can ask students to complete PA records to determine time spent in physical activities and to identify health-enhancing activities for classroom PA breaks. Community leaders, parents, and health care professionals can identify activity types that promote healthful behaviors. Public health agencies can use the METy values for surveillance and as a resource to inform progress toward meeting national physical activity guidelines. Applications for the private sector include the use of METy in PA trackers and other applications.Conclusion : The National Collaborative on Childhood Obesity Research Web site presents the Youth Compendium and related materials to facilitate measurement of the energy cost of nearly 200 physical activities in children and youth. The Youth Compendium provides a way to standardize energy costs in children and youth and has application for a wide variety of audiences.